Model Simulation of “Sawah-Kolam” System for Rainwater Harvesting to Support Rainfed Paddy Production - Sugeng Triyono; . Zeovany; . Oktafri; Bustomi Rosadi (UNIVERSITY OF LAMPUNG, 2010)
Model Simulation of “Sawah-Kolam” System for Rainwater Harvesting to Support Rainfed Paddy Production (S Triyono, Zeovany, Oktafri, and B Rosadi): The study was used to evaluate whether rainwater could be harvested and used to meet water demand of rainfed paddy. As generally known, yield of rainfed paddy was low compared to that of irrigated paddy. The study was performed by simulating a model of “Sawah-Kolam” system. Daily 10 year climatological data from Metro City of Lampung Province was used in the study. The program was written in Professional VisSim 4.0. Three scenarios of alternative planting schedules (January, February, and March) were tested. Results implied that without a collection system, rainwater might not be sufficient to grow rainfed paddy. It was demonstrated that “Sawah-Kolam” system was capable of sufficing water requirement of rainfed paddy. Huge rainwater of more than 90% could be saved, thus reducing a lot of runoff volume. In term of pond size, February appeared to be the most optimum growing season of all other months for Metro City, in that the pond area (1,400 m2) required was the smallest.